2020
DOI: 10.18182/tjf.693299
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of dune biotopes, the case of Kurucaşile (Bartın)

Abstract: Kumul biyotoplarının haritalanması, Kurucaşile (Bartın) örneğiBurçin Ekici a,* Özet: Günümüzde ekosistem yaklaşımlarında uzun dönemli başarının elde edilmesi, doğal kaynakların kullanımında sürdürülebilir bir planlama anlayışının geliştirilmesine bağlıdır. Bu kapsamda, biyotop haritalama çalışmalarına gereksinim duyulmaktadır. Bu araştırma ile Kurucaşile (Bartın)'nin kumul biyotopları haritalanarak, habitatlar ve flora varlığı hakkında detaylı veriler toplanmıştır. Araştırma, alana ilişkin mevcut çalışmaların … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Because of the spontaneity and statistics of social media data, it is confirmed that people are born with the perception of biodiversity [32]. Finally, cluster analysis and spatial coupling methods were used to summarize four preferred habitat types of typical urban wetland parks, and reasonable human intervention was carried out for different habitat types to improve biodiversity to a certain extent [29,77]. At the same time, with the promotion of social media, the computational dimension of the biodiversity experience is enriched, the ecological education function of urban wetland parks is strengthened, and the dynamic balance between recreation and conservation is expected to be achieved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the spontaneity and statistics of social media data, it is confirmed that people are born with the perception of biodiversity [32]. Finally, cluster analysis and spatial coupling methods were used to summarize four preferred habitat types of typical urban wetland parks, and reasonable human intervention was carried out for different habitat types to improve biodiversity to a certain extent [29,77]. At the same time, with the promotion of social media, the computational dimension of the biodiversity experience is enriched, the ecological education function of urban wetland parks is strengthened, and the dynamic balance between recreation and conservation is expected to be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…The establishment of a landscape structure index system, such as area, perimeter, edge complexity, and connectivity of habitat units, makes up for the deficiency of habitat space [24][25][26]. In recent years, the visualization of habitat units has been achieved with the aid of computer software [27][28][29]. Spatial data that can be easily measured and recorded enhances the operability of wetland habitat diversity assessment.…”
Section: Introductionmentioning
confidence: 99%